2020
DOI: 10.1098/rsta.2019.0494
|View full text |Cite
|
Sign up to set email alerts
|

Surface currents in the Alderney Race from high-frequency radar measurements and three-dimensional modelling

Abstract: Two weeks of high-frequency radar measurements collected at the Alderney Race are compared with the results of a three-dimensional fully coupled wave–current model. Spatial current measurements are rare in this site, otherwise well investigated through modelling. Thus, the radar measurements offer a unique opportunity to examine the spatial reliability of numerical results, and can help to improve our understanding of the complex currents in the area. Comparison of observed and modelled surface current velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…These works paved the way for more recent studies such as [15][16][17]. Very recently, and crucially for this paper dealing with the Alderney Race, the results of mainly two French research programs (THYMOTE and HYD2M) were published, most of them in a special issue of the Philosophical Transaction of the Royal Society A [18][19][20][21][22][23][24][25]. All these works will be extremely valuable for the forthcoming computations applied to farm configurations in the Alderney Race and specifically for the configuration treated in the present paper.…”
Section: Introductionmentioning
confidence: 93%
“…These works paved the way for more recent studies such as [15][16][17]. Very recently, and crucially for this paper dealing with the Alderney Race, the results of mainly two French research programs (THYMOTE and HYD2M) were published, most of them in a special issue of the Philosophical Transaction of the Royal Society A [18][19][20][21][22][23][24][25]. All these works will be extremely valuable for the forthcoming computations applied to farm configurations in the Alderney Race and specifically for the configuration treated in the present paper.…”
Section: Introductionmentioning
confidence: 93%
“…Another practical way of assessing the space–time variability of circulation in the Alderney Race is the remote sensing of surface currents by HF radars. We decided to present in this section only one example of the radar-derived velocity field in order to highlight the capabilities of this technique to capture the spatial structure of the flow in detail (for further results the reader is referred to [41]). Figure 11 shows a snapshot of surface current velocities during peak flood flow on July 9, 15.00 UTC.…”
Section: Preliminary Results Of Datamentioning
confidence: 99%
“…Thus, techniques of noise removal, despiking and gap filling were applied to remotely sensed data before reconstructing the radial velocity time series. The detailed description of the radar network configuration and methods of data processing can be found in [40,41].…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Comparisons between radar surface current measurements and ADCP derived near surface measurements typically exhibit a bias less than 0.03 m s −1 and RMSE less than 0.10 m s −1 (Lopez, 2017). Whilst radar-derived currents are extensively used for oceanographic studies in coastal regions (e.g., Lopez et al, 2020;Paduan & Washburn, 2013), whether they include either the entire wave-induced Stokes drift, part of it or none of it is still an open question (e.g., Isern-Fontanet et al, 2017) Assessment against independent observations showed that modeled wind data might be affected by large inaccuracies in shelf and coastal areas. This is in agreement with other studies.…”
Section: Assessment Of the Lagrangian Modeling Approachmentioning
confidence: 99%